2021
DOI: 10.1038/s41375-021-01408-w
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning detects acute myeloid leukemia and predicts NPM1 mutation status from bone marrow smears

Abstract: The evaluation of bone marrow morphology by experienced hematopathologists is essential in the diagnosis of acute myeloid leukemia (AML); however, it suffers from a lack of standardization and inter-observer variability. Deep learning (DL) can process medical image data and provides data-driven class predictions. Here, we apply a multi-step DL approach to automatically segment cells from bone marrow images, distinguish between AML samples and healthy controls with an area under the receiver operating character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 45 publications
(43 reference statements)
1
45
0
Order By: Relevance
“…We found that using only slide-level labeling without detailed pixellevel or cellular annotation enables interpretable, highperformance diagnostics, which overcomes the cost of labeling and closely resembles clinical applications. We collected a large collection of bone marrow smear WSIs and used them for training, which has more information than training a model using an expert-selected ROI (24,26,45) and allows for full automation. Simultaneously, we demonstrate that no adjustments are required and can be applied to the micrograph analysis of bone marrow or peripheral blood, which addresses the high imaging cost in certain resource-poor regions.…”
Section: Discussionmentioning
confidence: 99%
“…We found that using only slide-level labeling without detailed pixellevel or cellular annotation enables interpretable, highperformance diagnostics, which overcomes the cost of labeling and closely resembles clinical applications. We collected a large collection of bone marrow smear WSIs and used them for training, which has more information than training a model using an expert-selected ROI (24,26,45) and allows for full automation. Simultaneously, we demonstrate that no adjustments are required and can be applied to the micrograph analysis of bone marrow or peripheral blood, which addresses the high imaging cost in certain resource-poor regions.…”
Section: Discussionmentioning
confidence: 99%
“…This should be considered when planning similar studies. The occlusion-based explanations pointing to critical structures represent a useful tool for fine-tuning and optimization of neural networks in histopathology, and potentially for identification of previously unrecognized morphological features related to histopathological diagnosis, prognosis, and prediction [23, 24]. Finally, unravelling the large quantity of features within the network and exposing the key elements will help to promote trust in these and similar AI-based methods in pathology, enhancing the opportunities for incorporation into clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Recent applications of computational cytomorphology on bone marrow smears have demonstrated its ability to automatically identify different leukocytes 30,62 and assist diagnostic predictions [27][28][29] in specialized haemato-oncology. By demonstrating that this can now be extended to blood smears/slides, our work reveals the potential for the large-scale incorporation of automated cytomorphology into routine diagnostic workflows.…”
Section: Discussionmentioning
confidence: 99%
“…Computational methods, which have shown promise in the characterization and prediction of MDS and AML using bone marrow slides [27][28][29] and identification of abnormal leukocytes 30 , can help address these problems.…”
Section: Introductionmentioning
confidence: 99%